Role of miRNAs in Normal and Myasthenia Gravis Thymus - Cron, Mélanie A.; Guillochon, Émilie; Kusner, Linda; Le Panse, Rozen (Frontiers in Immunology, 2020)
The thymus, a primary lymphoid organ, provides a complex environment essential for the generation of the T-cell repertoire. Thymic alterations occur during life either in the context of thymic involution upon aging or the pathophysiological context of Myasthenia Gravis (MG). These changes involve complicated regulatory networks, in which microRNAs (miRNAs) are key players. Here, we analyzed the role of miRNAs in thymocyte maturation and differentiation sustained by thymic epithelial cells. We compared data from the literature regarding the role of mouse thymic miRNAs and original data obtained from a human thymic miRnome study. We identified a set of highly expressed miRNAs defined as ThymiRs and investigated miRNA expression in infants as compared to adults to determine those associated with human thymic involution. Thymic changes are also frequently observed in MG, an autoimmune disease which results in the production of anti-acetylcholine receptor (AChR) antibodies that lead to muscle weaknesses. Alterations such as thymoma in late-onset MG patients and hyperplasia with ectopic germinal centers (GCs) in early-onset (EOMG) patients are found. . Thymic miRNA expression has been studied in AChR-MG patients both in thymoma-associated MG (TAMG) and EOMG, and their function through their mRNA targets investigated. Most of the dysregulated thymic miRNAs in EOMG are associated with GC development, such as miR-7, miR-24, miR-139, miR-143, miR-145, miR-146, miR-150, miR-452, miR-548 or thymic inflammation, such as miR-125b, miR-146, or miR-29. Understanding these pathways may provide therapeutic targets and biomarkers of disease manifestations.